Numerical Analysis of a Flow over a Naca0015 Airfoil Containing the Flap and Gurney Flap Elements (International Journal of Scientific Research and Management (IJSRM), 2022)
The present work aimed at numerical simulation of a two-dimensional, incompressible and steady-state airflow over a NACA0015 airfoil with flap and Gurney flap using the standard turbulence models k-epsilon, k-omega and versions of these models with modified constants. All meshes used were structured. Comparison of the results of the turbulence models with experimental data from the literature shows differences between the results in the leading-edge region. The differences were minimized by adjusting the contents of the turbulence models. For validation, the k-epsilon turbulence model with modified constants was used in a new simulation of a profile (NACA0012), which agrees with several experimental studies; however, it does not show better results.